Globalisasi dan Mobilitas Manusia: Remitansi sebagai Penggerak Perekonomian di Amerika Latin dan Kepulauan Karibia - Raissa Ardianti (Department of International Relations, Brawijaya University, 2014)
Abstract Migration is the manifestation of people mobility in the globalization era. The developing of public transportation technology and the removing of visa requirements for some certain regions have encouraged migration as they trigger high level of people mobility. As a result, many people from developing countries decide to migrate in hope of getting better life. Developed countries open a very wide opportunity for skilled or professional workers from developing countries. According to Jagdish Bhagwati and Nicholas Van Hear, the importing of professional labors (and migration in general) to a great extent has brought only disadvantages for it may disrupt the country of origin’s balance of microeconomic condition. Yet, migration also results in several advantages, including the amount of remittances sent home by the immigrants. This paper aims to demonstrate that Bhagwati and Van Hear’s claims are hardly found in Latin America and the Caribbean as these regions obtained the advantage of migrationthrough remmitances, which succesfully supported the local economy. Keywords : people mobility, migration, remittances